Using a reassessment framework to determine critical case management needs: DRAOR improves on LS/RNR’s predictive discrimination of short-term recidivism - Coulter, Darcy J. (Psychology, crime & law, 2024)
Two core tasks within community corrections are estimating recidivism risk and providing supportive case management to supervised clients. Recent studies demonstrated that regularly reassessing dynamic risk factors enhances the predictive accuracy of case management tools that identify immediate client needs. Using a large sample (N = 2076) of adults on parole in an Australian jurisdiction, we evaluated whether reassessed versus initial scores from Level of Service/Risk, Need, Responsivity (LS/RNR) and Dynamic Risk Assessment for Offender Re-entry (DRAOR) better discriminated recidivists from non-recidivists. Using Cox regression survival analyses, we modelled risk for general and violent recidivism. Updated DRAOR scores incrementally predicted recidivism beyond initial scores, particularly showing that DRAOR Acute scores can identify needs related to immediate recidivism risk. Models combining LS/RNR criminal history scores with updated DRAOR Acute scores demonstrated the greatest predictive validity, suggesting case managers must consider acute dynamic risk factors within the context of long-term risk. We suggest that attending to criminal history, criminogenic needs and acute dynamic risk factors are each necessary for effective case management, with specific attention toward regularly reassessed acute dynamic risk factors among people identified with higher long-term risk and needs.